Patients with Premature Cardiovascular Diseases in Ambulatory Practice: Demographic Characteristics, Risk Factors and Adherence to the Medical Therapy (Data of RECVASA Registry) - E. Yu. Andreenkо; M. M. Loukianov; S. S. Yakushin; A. N. Vorobyev; K. G. Pereverzeva; V. A. Dindikova; A. N. Makoveeva; E. V. Kudryashov; S. A. Boytsov; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the gender characteristics, educational level, cardiovascular diseases (CVD) risk factors and adherence to drug treatment in patients with premature CVD in an outpatient prospective registerу.   Material and methods. 3690 patients with hypertension, coronary artery disease, chronic heart failure, atrial fibrillation and their combinations were enrolled in the RECVASA registry in Ryazan region of Russia. Groups of patients with early development of CVD (criterion 1 – the age of 18-49 years old, criterion 2 – the age of men 18-54 years old and women – 18-64 years old) were compared with the corresponding older groups. The gender characteristics, educational level, CVD risk factors, and adherence to drug treatment were analyzed.   Results. According to criterion 1, the age groups of 18-49 years old and ≥50 years old included 347 (9.4%) and 3343 (90.6%) patients, respectively, 144 (41.5%) and 902 (27, 0%), respectively were   men, p<0.0001. According to criterion 2, 1369 (37.1%) patients were assigned to the group with early development of CVD, of which 254 (18.6%) were men under 55 and 1115 (81.4%) were women under 65. The group of older patients included 2321 individuals, of which 792 were men (34.1%) and 1529 were women (65.9%). According to criterion 2, the proportion of men in the group of patients with early development of CVD, was 2.2 times lower, than in the older age group (18.6% vs 41.5%, respectively; p<0.0001). Patients <50 years old were more likely to have higher education, than the group of patients ≥50 years old (42.3 vs 25.9%; p<0.0001), including among both men and women. According to criterion 2, the same statistically significant differences were observed (36.2 vs 21.3%; p<0.0001), including among both men and women. The proportion of smokers was 2 times higher in patients younger than 50 years old, than in patients ≥50 years old (44.0 vs 21.7%; p<0.0001). The largest proportion of smokers was among men and women <50 years old (69.4% and 24.1%, respectively). According to criterion 1, hypercholesterolemia (>5 mmol/L) was diagnosed significantly less frequently in patients with early development of CVD than in the older age group (47.8 vs 54.6%; p=0.047); these differences were obtained due to women (46.9 vs 58.8%; p=0.008), the proportion of individuals with hypercholesterolemia did not significantly differ among men. According to criterion 2, statistically significant differences in the frequency of hypercholesterolemia were not detected among both men and women. There was no differences in the incidence of family history (FH) of premature CVD in the study groups, while the proportion of patients with FH of premature CVD was significantly higher in men <55 years old than in women <65 years old (44.8 vs 37.7%; p<0.0001). According to criterion 1 the proportion of patients with low adherence to treatment was higher in patients with early development of CVD than in the older age group (57.1% vs 46.1%; p=0.0006), the proportion of patients with high adherence was 22.9% and 32.4% (p=0.0013), respectively. According to criterion 2, there were no differences in adherence to treatment.   Conclusions. According to RECVASA registry, patients with early development of CVD were more likely to be men, in accordance with criterion 1. Patients with early development of CVD, including men and women, according to both criteria, were characterized by a significantly higher proportion of individuals with higher education and a higher proportion of smokers. In patients with early development of CVD using criterion 1, in contrast to criterion 2, hypercholesterolemia was diagnosed significantly less often than in the older age group. It is preferable to use criterion 1 to assess hypercholesterolemia in patients with early development of CVD. The proportion of individuals with FH of premature CVD was significantly higher in men <55 years old than in women <65 years old. Patients with early development of CVD according to criterion 1 were characterized by a lower adherence to drug treatment. Individuals with early development of CVD, especially <50 years old are the target group for comprehensive prevention, not only due to improving the quality of proven effective drug therapy, but also by correcting risk factors and increasing level of adherence to treatment.